1965
DOI: 10.1139/v65-100
|View full text |Cite
|
Sign up to set email alerts
|

PROTONATED CARBONYL GROUPS: V. Α-Pyridone SALTS

Abstract: Salts of 1-methyl-2-pyridone and 1-methyl-2-quinolone with strong acids have been prepared and their infrared spectra recorded between 4 000 and 650 cm−1. Protonation of the carbonyl group occurs giving rise to OH stretching, in-plane and out-of-plane bending vibrations which absorb in characteristic regions of the spectrum, namely 1 900 – 3 300 cm−1 (depending on the anion), ~ 1 250 cm−1, and ~ 800 cm−1 respectively, with appropriate shifts on deuteration. Other tentative assignments are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1966
1966
1984
1984

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The became controversial when Spinner originally concluded that protonation took place on the ring nitrogen atom leading to cations 3 and 4 (12). Spinner later revised these structures and agreed that they are correctly represented by 5 and 6, respectively (13,14,26,27). This project set o u t to compare the IR spectra of a number of salts of 2and 4-pyridones with those of closely related 2and 4-substituted pyridinium salts in order to obtain additional evidence for structures 5 and 6.…”
mentioning
confidence: 99%
“…The became controversial when Spinner originally concluded that protonation took place on the ring nitrogen atom leading to cations 3 and 4 (12). Spinner later revised these structures and agreed that they are correctly represented by 5 and 6, respectively (13,14,26,27). This project set o u t to compare the IR spectra of a number of salts of 2and 4-pyridones with those of closely related 2and 4-substituted pyridinium salts in order to obtain additional evidence for structures 5 and 6.…”
mentioning
confidence: 99%